Team Awkward - Birchall, Katy (Birchall, Katy. It girl, 2018)
When a video of her falling butt-first into a potted plant goes viral in her school, Anna determines to find her worthy "thing" to be famous for, and, more importantly, to attract her crush, Connor, away from the cute, artsy new girl. School sports day is coming up, and Anna thinks she can become team captain, and nothing can go wrong with that.